Stone Matrix Asphalt and silica-aerogel composite: mechanical and structural performance - Mohammad Namavar Jahromi; Alireza Sarkar (Results in Engineering)
Despite the desirable rutting resistance of Stone Matrix Asphalt (SMA) mixtures, their poor performance against thermal cracking, fatigue, and moisture damage remains a critical limitation in hot and humid environments. To address these issues, improving the bonding between aggregates and asphalt binders can enhance resistance to tensile stresses and reduce crack formation and fatigue. One practical approach is the incorporation of nanomaterials into asphalt mixtures. Nano Silica (NS) has shown promising results in improving binder-aggregate adhesion and enhancing asphalt mixture durability due to its high surface area and nano-scale particle size. Nano Silica Aerogel (NSA) exhibits similar beneficial properties to NS, such as improving resistance to fatigue, cracking, and moisture-induced damage. However, NSA also offers additional advantages, including ultra-low thermal conductivity and superior environmental compatibility, making it a novel additive for improving asphalt performance under severe climatic conditions. The present study primarily investigates the application properties of ultra-lightweight silica aerogel with nano-pores to Stone Matrix Asphalt (SMA). The materials used in this study include 85/100 penetration-grade (PG 58–22) asphalt binder, limestone aggregate, filler, Nano Silica Aerogel at three concentrations of 1, 2, and 3 % by asphalt binder weight, and cellulose fibers (in the control specimens). To assess the thermal stability, functional and mechanical properties of the modified SMA asphalt compared to control samples, a variety of tests were conducted, including thermogravimetric analysis, asphalt binder drain down, Marshall stability, flow, resilient modulus, moisture sensitivity, rutting, indirect tensile fatigue, and semicircular bending. As a result of the thermogravimetric analysis test, the addition of NSA increases the asphalt binder's thermal stability. In addition, the results of the mechanical test showed that adding 1 % nano-silica aerogel significantly improved the resilient modulus and extended the fatigue life. Samples containing 3 % of this material showed the most significant improvements in Marshall strength, moisture sensitivity, and rutting. Added nano silica aerogel to asphalt mixtures enhanced resistance to rutting by 49 %, fatigue life by 83 %, and Marshall strength by 50 %. Overall, adding this material improved the performance of uncracked asphalt mixtures and significantly reduced the load capacity of cracked samples.